Evaluasi Desain Media Sosialisasi Kebencanaan Ditinjau dari Kemampuan Literasi Visual (Studi Kasus Media Sosialisasi Tsunami Kabupaten Bantul Yogyakarta) - Danang Febriyantoko; Naomi Haswanto; Y. Martinus Pasaribu (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2012)
There society requires an adequate understanding of disaster risk in order to react appropriately to save themselves. The role of disaster media socialization as one source of information is an important element in disaster management. Understanding disaster media socialization reflects community level preparedness in an area. This research is the study of visual literacy measured to evaluate the tsunami socialization media given to the coastal districts of Bantul, Yogyakarta. From the research facts about the level of literacy communities are affected by the social and cultural environment. Based on the results the easy disaster media needed to be found in relation to daily in order to foster disaster preparedness.